2022
DOI: 10.1021/acs.cgd.2c00982
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural Effects in the Square Lattice (sql) Topology Coordination Network Sql-1-Co-NCS·4OX

Abstract: A high-pressure study of a switching coordination network of square lattice topology (sql) loaded with o-xylene (OX), [Co(4,4′-bipyridine) 2 (NCS) 2 ] n •4nC 8 H 10 (sql-1-Co-NCS•4OX), was conducted up to approximately 1 GPa to investigate pressure-induced structural changes. Previous reports revealed that sql-1-Co-NCS exhibits multiple phases thanks to its ability to switch between closed (nonporous) and several open (porous) phases in the presence of various gases, vapors, and liquids. Networks of such prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…[29][30][31][32] Recently, we reported that the previously known square lattice (sql) CN, 33,34 [Co(bpy) 2 (NCS) 2 ] n (bpy = 4,4′-bipyridine), sql-1-Co-NCS, exhibits recyclable switching between its "closed" nonporous and "open" porous phases induced by CO 2 or C 8 aromatics. 35,36 We coined the term "switching adsorbent layered materials" (SALMAs) for such sorbents and they hold promise for gas storage and hydrocarbon separations, [36][37][38][39][40][41][42] prompting us to explore the feasibility of their large-scale manufacture. In our previous work, 35 we prepared sql-1-Co-NCS by applying heat under vacuum to its guest-loaded variant sql-1-Co-NCS•2TFT (TFT = α,α,α-trifluorotoluene), which was synthesized by self-assembly of Co(NCS) 2 and bpy using the SD method in the presence of organic solvents (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Recently, we reported that the previously known square lattice (sql) CN, 33,34 [Co(bpy) 2 (NCS) 2 ] n (bpy = 4,4′-bipyridine), sql-1-Co-NCS, exhibits recyclable switching between its "closed" nonporous and "open" porous phases induced by CO 2 or C 8 aromatics. 35,36 We coined the term "switching adsorbent layered materials" (SALMAs) for such sorbents and they hold promise for gas storage and hydrocarbon separations, [36][37][38][39][40][41][42] prompting us to explore the feasibility of their large-scale manufacture. In our previous work, 35 we prepared sql-1-Co-NCS by applying heat under vacuum to its guest-loaded variant sql-1-Co-NCS•2TFT (TFT = α,α,α-trifluorotoluene), which was synthesized by self-assembly of Co(NCS) 2 and bpy using the SD method in the presence of organic solvents (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2D sql CNs with general formula [M­(L) 2 (A) 2 ] n (M = divalent metal cation, L = ditopic linker ligand, A = axial counteranion) are modular from a crystal engineering perspective and exemplify the “node and linker” design strategy proposed by Hoskins and Robson over three decades ago. , The first reported sorption study for 2D switching sql CNs was conducted on [Cu­(bpy) 2 (BF 4 ) 2 ] (bpy = 4,4′-bipyridine), ELM-11, which was observed to exhibit single (type F–IV s ) or multistep (type F–IV m ) sorption isotherms (Scheme a, d) induced by gases such as N 2 , Ar, CO 2, C 2 H 2 and n -butane. ,,,, Recently, we studied the sorption properties of three previously known sql CNs [M­(bpy) 2 (NCS) 2 ] n (M = Fe, Co, or Ni), sql-1-M-NCS, which are closely related to the ELM platform. CO 2 sorption for sql-1-M-NCS resulted in single-step type F–IV s isotherms (Scheme a) and the switching pressures were found to be metal-ion controlled with the Ni version being the “softest”. , It was later reported that sql-1-Ni-NCS exhibited even lower switching pressure and higher sorption uptake for C 2 H 2 than for CO 2 …”
mentioning
confidence: 99%
“…42 Future studies will explore the sorption behaviour of sql-1-Ni-NCS and related switching adsorbent layered materials (SALMAs) for other adsorbates including the effect of pressure. 43…”
mentioning
confidence: 99%
“…42 Future studies will explore the sorption behaviour of sql-1-Ni-NCS and related switching adsorbent layered materials (SALMAs) for other adsorbates including the effect of pressure. 43 M. J. Z. gratefully acknowledges the support of the Irish Research Council (IRCLA/2019/167) and Science Foundation Ireland (16/IA/4624).…”
mentioning
confidence: 99%